Short Communication: Traditional medicinal formulation: Obat pahit from Lingga Malay Ethnic in Riau Archipelago, Indonesia - FITMAWATI FITMAWATI; NERY SOFIYANTI; RODESIA MUSTIKA ROZA; ISNAINI ISNAINI; HIDAYATUL HAZIMI; YULISA RESTI IRAWAN; DHANIEL RIDHO WINATA; AWAL PRICHATIN KUSUMO DEWI (Biodiversitas Journal of Biological Diversity, 2017)
Fitmawati, Sofiyanti N, Roza RM, Isnaini, Hazimi H, Irawan YS, Winata DR, Dewi APK. 2017. Traditional medicinal formulation: Obat pahit from Lingga Malay Ethnic in Riau Archipelago, Indonesia. Biodiversitas 18: 1196-1200. Lingga Malay Ethnic is the native ethnicity in the Lingga District, Riau Archipelago, Indonesia. This ethnic still holds strong beliefs of their ancestors, such as the use of medicinal plants. One ingredient that is still used today is obat pahit as a body fitness keeper. The aim of this research was to inventory the kinds of medicinal plants used by Lingga Malay ethnicity in obat pahit potions. This research was conducted using survey and observation methods on the packaging of obat pahit. Interviews were held on Traditional Medicine Practitioners (TMP) of 5 (five) people TMPs using a questionnaire form. The research results during the interview and observation of TMPs in the packaging of obat pahit showed the differences in number and kinds of plants of each TMP. The interview results which were obtained 2 plant species were listed from Kalan TMP; SP4 TMP is about 12 species of plants; Linau TMP is 14 species of plants; Resun TMP is 7 species of plants; and Musai TMP is 14 species of plants. The dominant medicinal plants that are used on this study were Bauhinia semibifida, Cnestis sp. and Cnestis palala.